A REVIEW ON HERBAL IMMUNITY BOOSTERS FOR IMPROVEMENT OF HUMAN HEALTH IN COVID-19 - Surabhi Shakya; Padmini Shukla; Prabodh Shukla (Journal of Biomedical and Pharmaceutical Research, 2020)
Herbal immunity boosters are the medicinal plants which increase the immunity of the human body and make the body able to fight with the various diseases. These immunity boosters are serving as a boon in the case of coronavirus disease. COVID-19 affects our respiratory system and lowers the immunity of the patient and the persons having weak immunity have the more chances to get affected with the diseases. Tulsi, garlic, ginger, giloy, coconut oil, turmeric, ashwagandha, amla, black pepper, aloevera are the herbal immunity boosters. These herbal drugs used traditionally in medicines and also proved effective in scientific studies. The regular consumption of these boosters helps to treat the mild to moderate symptoms of diseases at home. Keywords: Herbal immunity boosters, Coronavirus, COVID-19, Garlic, Tulsi, Ginger, Aloe vera